Lower-limb extension power: How well does it predict short distance speed skating performance? - Liebermann, D. G.; Maitland, M. E.; Katz, L. (Isokinetics and Exercise Science, 2002)
Purpose: This study was aimed to explore the relationship between lower limb extension power measured by isokinetic knee extensions (IK) and vertical jumps performed on a force plate (VJ) and speed skating (SS) sprint power measured by a laser device. Methods: Twenty elite short- and long-track speed skaters performed 100 m sprints followed by VJ and IK trials. Power-time curves were calculated off-line. Pearson correlation coefficients were used to determine the degree of association between the variables. Results: SS sprint power correlates strongly with VJ power (r=0.870; p<0.001) while IK power showed a weaker but significant correlation to both (r=0.707 and r=0.706, respectively; p<0.01). As expected, SS times at 15 m and 100 m were inversely associated with SS sprint power (r=-0.818 and r=-0.909; p<0.001) and VJ power (r=-0.730 and r=-0.763; p<0.001), and to a lesser degree with IK power (r=-0.602; r=-0.618; p<0.01). Conclusion: The analyses differentiate between methods of estimating power in speed skaters, and show a strong relationship between initial SS performance and muscular power. Given that 100 m split times strongly relate to final 500 m results (r=0.972; p<0.001, N=332), it is reasonable to believe that an initial power and a stable peak speed before the first curve may lead to achieving the winning edge in short SS events. A finding of particular interest is that isokinetic power results are correlated significantly with the practical outcomes of the performance in spite of the high specificity of the isokinetic testing method.